THE TRANSITIVITY AS A GENROLOGICAL FACTOR OF INTERTEXTUALITY - Tychinina, Alyona; Namestiuk, Svitlana; Vilchanska, Yulia (ВІСНИК МАРІУПОЛЬСЬКОГО ДЕРЖАВНОГО УНІВЕРСИТЕТУ СЕРІЯ: ФІЛОЛОГІЯ, 2020)
The transitivity of the plot in the aspect of the reception theory exposed the phenomenon of culturological transit, which has its own laws – actually cover the receptive segment of literary science. The article emphasizes the functions of the narrator in creating the personosphere when generating a classical plot. The types of narratives have been selected in M. Bulgakov’s works. The triple argumentation of the receptive theory allows exploring the process of the immanent perception of canonical artistic text. In our case, by studying the existing versions (generative models) of Bulgakov’s «Master and Margarita», we adhere to the signposted methodological contour
Keywords: he transit of tradition, classical plot, personosphere, narrative, genre, sequel, M. Bulgakov, V. Ruchinsky, V. Kulikov, Ch. Aitmatov